PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP INTERAKSI SOSIAL SISWA KELAS X IIS SMA NEGERI 12 PEKANBARU TAHUN AJARAN 2014/2015 - Desy Utami Ningsih Utami Ningsih; Tri Umari Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The ability of social interaction is very important especially for a student, because the humans are basically created as social beings who are always wiil live in a relationship with other individuals. Therefore in humans should be able to cooperate with others. This study aims to determine The Effect Of Group Counseling Services To Students Learning Interaction Of Grade X IIS SMA Negeri 12 Pekanbaru Year Academic 2014/2015.In type of experience is used in this research is pre-experimental with one group pre-test post-test. The subjects in this experience is 30 students who have low social interaction skills in category medium. From the calculations of data analysis, it was obtained that the thitung is greater than ttabel with (-14.24 > 2,000). So it means that Ho is rejected and Ha accepted which means there is a very significant of social interaction skills difference between before and after the experiment by Group Counseling Services To Students Of Grade X IIS SMA Negeri 12 Pekanbaru. Keyword : Group guidance, social interaction